Leadership and management in Estonian academic libraries: leaders’ role and competencies. - Mandre, Sigrid (Qualitative and Quantitative Methods in Libraries, 2017)
There is a lot of research about academic library leadership. This research includes different sides of leaders’ activities, functions and characteristics. In most studies top leaders are examined. Only few studies have been done about middle managers. This study was designed to include both top and middle level leaders. The goal is to investigate the views and understanding of different level leaders on their own and the other level leaders’ activities and competencies, needed for accomplishing the role of the leader. The presumption of the study is that leaders of all levels constitute a team, and therefore need distinct understanding of the role of other team members in the library leadership process. The goal is to investigate different levels leaders’ views and understanding of their own and the other level leaders’ activities and competencies, needed for accomplishing the leader’s role. The presumption of the study is that leaders of all levels constitute a team, and therefore need distinct understanding of other team member’s role in the library leadership and management process. The additional research issue is the education of leaders. Is it important, that the academic library leader has a degree in library and information sciences or there is no need for professional educational? The research strategy used in this study is the grounded theory. The grounded theory is seldom used in academic library leadership studies. The grounded theory is a qualitative method of social research. It gives an opportunity to analyse and understand deeper the meaning that participants give to the role and competence of academic library leaders. Leaders at different levels have the role what includes specific competencies and all these roles and competencies have their purpose and place in the leadership and management process. The use of Grounded Theory in the pilot study of the research is described.